2010
DOI: 10.1080/09603101003636188
|View full text |Cite
|
Sign up to set email alerts
|

Forecasting accuracy of stochastic volatility, GARCH and EWMA models under different volatility scenarios

Abstract: The forecasting of the volatility of asset returns is a prerequisite for many risk management tasks in finance. The objective here is to identify the volatility scenarios that favour either Generalized Autoregressive Conditional Heteroscedasticity (GARCH) or Stochastic Volatility (SV) models. Scenarios are defined by the persistence of volatility (its robustness to shocks) and the volatility of volatility. A simulation experiment generates return series using both volatility models for a range of volatility sc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(12 citation statements)
references
References 26 publications
0
12
0
Order By: Relevance
“…In addition to the above volatility models, we examine the out‐of‐sample performance of the exponentially weighted moving average (EWMA) volatility model often used in practice to calculate VaR by RiskMetrics. This model can be thought of as a special case of the GARCH model (see, for example, Ding and Meade, ).…”
Section: Empirical Analysismentioning
confidence: 99%
“…In addition to the above volatility models, we examine the out‐of‐sample performance of the exponentially weighted moving average (EWMA) volatility model often used in practice to calculate VaR by RiskMetrics. This model can be thought of as a special case of the GARCH model (see, for example, Ding and Meade, ).…”
Section: Empirical Analysismentioning
confidence: 99%
“…Moreover, the decay parameter should be adjusted in function of the time horizon. Ding and Meade (2010) point that EWMA exhibits a greater forecasting accuracy to real data compared to GARCH and SV models. González-Rivera et al (2004) found EWMA brings good results in the option pricing context.…”
Section: Introductionmentioning
confidence: 93%
“…We take the last k (k = 6, 12, 18, 24, 30, 36) data points of time series x as time series Y (collections of time series) respectively. Fitting features are these values which are the difference between the last element of time series x and the smoothed values of each time series of Y after Moving Average Algorithm [13], Weighted Moving Average Algorithm [14], Exponential Moving Average Algorithm [15] and Double Exponential Moving Average Algorithm [16]. There are over 30 statistical features after time-series features extraction.…”
Section: Time-series Features Extractionmentioning
confidence: 99%